(untitled) (Research, Society and Development, 2023)
Mantle cell lymphoma is a rare and aggressive mature B-cell non-Hodgkin lymphoma (NHL) with historically low long-term survival rates. The objective of the study was to outline the epidemiological profile of patients diagnosed with Mantle Cell Lymphoma treated at a reference cancer hospital. An observational, descriptive, cross-sectional study was carried out, with analysis of hospital records. Most patients were male, aged between 60 and 69 years and in stage IV. There was a predominance of patients with B symptoms. In laboratory terms, the patients had elevated lactic dehydrogenase and leucometry. No correlation was identified between age, lactic dehydrogenase and leukometry with mortality, on the other hand, there was a positive correlation with staging. All subjects had high-risk MIPI stratification. All first-line therapies were based on chemotherapy associated with the anti-CD20 monoclonal antibody – Rituximab. The second-line therapies used were: DHAP and GDP. Half of the patients underwent a second line of treatment. 100% of the patients studied did not undergo autologous transplantation, which may have influenced the status of patients in which 60% died. Future studies are needed to establish the impact on patient survival from changes in applied therapy such as increased exposure to autologous transplantation or use of covalent inhibitors of Bruton’s tyrosine kinase (BTK).